2017
DOI: 10.4236/jct.2017.812095
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors for Recurrence after Curative Resection for Colorectal Cancer

Abstract: Purpose: To identify clinical predictors of recurrence of colorectal cancer after curative surgical treatment. Methods: Retrospective follow-up-study of 925 consecutive patients treated with R0-resection for colorectal cancer Stage I, II and III from 1990 until 2000 with a mean follow-up of 60 ± 37 months. Predictors for cancer recurrence were identified in a pilot-sample of these patients, followed by analyses of the rest of the patients (test-sample), and finally with a concluding analyses of the entire pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…The reoperation rate of 9.3% was similar to other studies, reporting reoperation rates of 5% -10% after rectal cancer surgery and leak rates in colorectal and colo-anal anastomoses of 5% -19% [19] [20]. In a previous study, reoperation after surgery for colorectal cancer was associated with increased frequency of cancer recurrence [21]. This is also supported by studies from Kulu et al and Ptok et al, reporting an increase in recurrence rate and reduced survival rate in patients with anastomotic leaks after curative resection for rectal cancer [22] [23].…”
Section: Discussionsupporting
confidence: 86%
“…The reoperation rate of 9.3% was similar to other studies, reporting reoperation rates of 5% -10% after rectal cancer surgery and leak rates in colorectal and colo-anal anastomoses of 5% -19% [19] [20]. In a previous study, reoperation after surgery for colorectal cancer was associated with increased frequency of cancer recurrence [21]. This is also supported by studies from Kulu et al and Ptok et al, reporting an increase in recurrence rate and reduced survival rate in patients with anastomotic leaks after curative resection for rectal cancer [22] [23].…”
Section: Discussionsupporting
confidence: 86%
“…[10] The patterns and predictors of LR after curative resection have been investigated to optimize the therapeutic regimen and postoperative surveillance. Liska et al [11] proved that tumor stage, bowel obstruction, margin involvement, lymphovascular invasion, and local tumor invasion were significantly associated with colon cancer LR, and Rokke et al [12] further demonstrated that reoperation for postoperative complications, other than anastomotic leakage, was a significant predictor of LR of CRC. Although recent advances in molecular characterization of CRC have identified prognostic and predictive biomarkers for disease recurrence, [13][14][15] the pattern of genomic evolution between paired primary and LR CRC tissues and molecular evidence for the origin of recurrence are still unclear.…”
Section: Introductionmentioning
confidence: 99%